Mechanical performance of hybrid double- and step-lap joints in primary metallic aircraft structures: An experimental and numerical approach - Amir Ekladious; John Wang; Nabil Chowdhury; Wing Kong Chiu (Composites Part C: Open Access)
Hybrid joints, combining adhesive bonding with mechanical fasteners, address the limitations of traditional joining methods in restoring the integrity of aircraft structures. This study evaluates the static strength of double- and step-lap joint configurations, representing repairs in thin and thick metallic aircraft structures, through experimental testing and finite element analysis. Aerospace-grade 7075-T6 aluminium alloy was used for the adherends, with film adhesives and fasteners arranged in typical airframe patterns. The three-dimensional finite element (FE) models incorporated non-linear adhesive properties, fastener preload, contact interactions, and frictional forces. The FE results aligned well with experimental findings, capturing key failure modes and load distributions. Hybrid double-lap joints exhibited strength comparable to bonded joints while mitigating their brittle failures through fasteners that provided additional load-bearing capacity. In thicker step-lap joints, the hybrid configuration nearly restored the parent material’s inherent stiffness, with a moderate strength reduction due to the reduced bond area from the bolt holes, while enhancing elongation capabilities and resistance to localised stress concentrations. Stress analyses highlighted a transition from adhesive-dominated to fastener-dominated load transfer under high loads, demonstrating key interplay between adhesive and mechanical fasteners in hybrid joints. This study presents part of a systematic assessment of the mechanical performance and damage tolerance of the hybrid joining technique, compared with adhesively bonded and mechanically fastened methods, in metallic aircraft structures.